1978
DOI: 10.1002/bjs.1800650909
|View full text |Cite
|
Sign up to set email alerts
|

The fibrinogen uptake test after hip surgery

Abstract: The fibrinogen uptake test has been used to detect deep vein thrombosis after total hip replacement in 90 patients. The upper third of the thigh in each leg was ignored and peripheral leg counting carried out distal to this. The results were directly compared with the findings of venography in the 170 legs of the 90 patients. There was a high false positive rate (30 per cent) with the fibrinogen uptake test which was associated with the presence of the knee joint effusion or varicose veins, but not with the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1985
1985
1993
1993

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…It is important to note that, in assessing the incidence of DVT, our study utilized venography -a technique which is considered to be the most accurate method available for the detection of this condition (Browse, 1978). Various other studies have used the fibrinogen uptake test, which is very inaccurate after hip surgery, with a false positive rate of approximately 30% (Louden et al, 1978) and a false negative rate of between approximately 8 % (Field, Kakkar and Nicolaides, 1972) and 18% (Morris and Mitchell, 1977). It is also of little value in the detection of thrombi above the knee (Morris and Mitchell, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that, in assessing the incidence of DVT, our study utilized venography -a technique which is considered to be the most accurate method available for the detection of this condition (Browse, 1978). Various other studies have used the fibrinogen uptake test, which is very inaccurate after hip surgery, with a false positive rate of approximately 30% (Louden et al, 1978) and a false negative rate of between approximately 8 % (Field, Kakkar and Nicolaides, 1972) and 18% (Morris and Mitchell, 1977). It is also of little value in the detection of thrombi above the knee (Morris and Mitchell, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…This reduces the value of the test as a screening procedure, as the incidence of DVT in this region has been found to be more than 10% (11). The incidence of false negative results has been found to be between 15% and 28%, and only Loudon et al (11) demonstrated an incidence smaller than 5%. We find that the relative high incidence of false positive results and the fact that the upper third of the femur is not evaluable makes the 123Ifibrinogen uptake test useless in detecting DVT in non-symptoma tic, elective orthopaedic patients.…”
Section: Discussionmentioning
confidence: 97%
“…In some of these studies ascending phlebography was used for definitive diagnosis of DVT. How ever, only few investigations have evaluated the i:bI-fibrinogen uptake test compared with phlebography in non-symptomatic, elective orthopaedic patients (11,12,13,14). Moreover, the test has not been employed on the upper third of the femur in these studies due to the high number of false positive results in this area (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 22 studies were retrieved that evaluated the predictive value of an abnormal leg scan result by direct comparison with venography. Of these, eight studies were classified as level L (13)(14)(15)17,18,21,25,26), and 14 as level 2 (Table 4) (9-11, 14, 2224, [27][28][29][30][31][32][33]. More than 2,500 legs were screened by leg scanning in level 1 studies; an abnormal leg scan result was obtained in 543 of which 531 (98%) had a venogram which was adequate for interpretation.…”
Section: Positive Predictive Value Studies In Orthopedic Surgical Patmentioning
confidence: 99%